(untitled) (Oratio Directa, 2025)
Each country develops a communication system in accordance with its social needs, political structure, and technological development. This literature review examines the position of Pancasila as the normative foundation of the Indonesian communication system and discusses its operationalization in the digital era. Secondary data were drawn from books, journal articles, legal documents, and relevant digital sources, then organized, reviewed, compared, and interpreted qualitatively. The review indicates that Indonesia's communication system has changed with political leadership and media development, while Pancasila has not always been translated consistently into institutional practice. A Pancasila-based communication system is open but links freedom to religious, humanitarian, national, deliberative, and social-justice responsibilities. Its practical agenda includes ethical public communication, accountable media governance, equal access to information and digital infrastructure, protection of personal data, public participation, and stronger digital literacy. Because the study relies on a narrative literature review and does not test an empirical model, its conclusions constitute a normative synthesis that requires further policy and field research.